Integration of Western and Islamic Epistemology in Islamic Education for the Formation of Moderate Character in Students: Integrasi Epistemologi Barat dan Islam dalam Pendidikan Islam untuk Pembentukan Karakter Moderat Peserta Didik - Rahmi, Aulia Afriana; Aurel Alsha Pradipta; Syaili Rizqoh; Muhammad Hufron (Averroes: Journal for Science and Religious Studies, 2025)
Research Background: This article discusses the integration of Western and Islamic epistemology  in Islamic education as a strategy for shaping moderate character among students amid the  challenges of globalization and the dichotomy of knowledge. The focus of this study is how Islamic  revelatory values can be synergized with Western rationality and empiricism in educational  practice. The research question addressed includes the lack of empirical studies on the implementation of this epistemological integration in the curriculum and teaching methods of  Islamic educational institutions.Methods: This research employs a qualitative approach through literature review using a descriptive-analytical method.  The key findings: indicate that integrative approaches, such as the use of contextual and value based learning, can shape students' characters to be tolerant, fair, and open-minded.  Contribution: This article contributes the concept of a transintegrative paradigm that unites  revelation and reason pedagogically to form individuals who are religious, rational, and humanistic.  Conclusion: the integration of Western and Islamic epistemology is important for realizing holistic  and contextual Islamic education. Such education can produce a generation that is not only  intellectually intelligent but also morally mature and ready to live in a pluralistic society.